FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN TOTAL ASET PERBANKAN SYARIAH DI INDONESIA - Rani Tri Aryanti; ROFIUL WAHYUDI (Journal of Global Business and Management Review, 2022)
This study aims to determine the internal and external factors that affect the growth of total Islamic banking assets in Indonesia. The data used in this study came from the published financial statements of each Islamic bank. The analytical method used in this study is annual time series data from 2016 to 2020. This study uses a causal quantitative approach. The sampling technique used is purposive sampling. The variables used in this study are Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), Third Party Funds, Gross Domestic Product, Interest Rates, and Inflation. The analytical method used is Multiple Linear Regression Analysis. The results showed that partially internal factors, only CAR and DPK , had a significant effect on the growth of total assets; simultaneously, internal factors had a significant effect on the growth of total assets. Then the research results on external factors partially do not affect the growth of total Islamic banking assets. At the same time, it simultaneously does not affect the growth of total Islamic banking assets.